PENGARUH PEMBELAJARAN KONTEKSTUAL BERBASIS MULTIPLE INTELLIGENCE TERHADAP KARAKTER DAN HASIL BELAJAR PKn - Ratnasarianti, Eka; Andi Sugiati; Hidayah Quraisy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the effect of contextual learning based on multiple intelligence on the character and learning outcomes of Civics Class V Elementary School Region II Students, Liukang Tangaya District, Kab. Pangkep. This research is a quantitative research type of quasi-experimental design research with the form of a nonequivalent control group design. The data obtained were analyzed using the SPSS v.26 application by looking for the results of the normality test, homogeneity test and Independent Sample t-Test to test the hypothesis. Based on the analysis of research data, the results provide conclusions: (1) There is an influence of contextual learning based on multiple intelligence on the character of Class V students of Region II Elementary School, Liukang Tangaya District, Kab. Pangkep. (2) There is an influence of contextual learning based on multiple intelligence on the Civics learning outcomes of Class V Elementary School Region II Students, Liukang Tangaya District, District. Pangkep. (3) there is an influence on the character and learning outcomes of Civics Class V Elementary School Region II students who are taught using contextual learning based on multiple intelligence with a higher average score difference than students taught using the direct learning model.